Knowledge and attitudes on oral health of women during pregnancy and their children: an online survey - Maria Grazia Cagetti; Claudia Salerno; Andrei Cristian Ionescu; Serena La Rocca; Nicole Camoni; Silvia Cirio; Guglielmo Campus (BMC, 2024)
Abstract Background Life-long healthy behaviors are established during pregnancy and the first years of life. In this cross-sectional survey, new mothers with a high level of schooling living in Northern Italy (Lombardy Region) were interviewed to assess their knowledge and attitudes towards their and child oral health. Methods A questionnaire (27 items) was developed to assess socio-demographic factors, knowledge, and attitudes towards maternal and child oral health. The questionnaire was disseminated in perinatal courses, private gynecological clinics, and via social media. Mothers aged ≥18 years, with at least a child aged 0-36 months, with a high school diploma or higher, were included in the survey. Results A total of 1340 women completed the questionnaire, 1297 of whom had a child aged 0-36 months, 792 lived in Lombardy, and 600 had a high level of education and were finally included. About half of the sample (44.67%) was aged between 31 and 35 years, 76.50% were employed, and the majority had only one child (81.50%). During pregnancy, 28.33% of the sample reported problems with teeth and gums, while only 36.00% visited a dentist. More than 40% of the sample said they were not aware of a possible link between oral health and pregnancy, and 73.17% had not received any advice about their oral health or the future health of their baby's mouth. Less than 20% of women were aware of the increased caries risk associated with prolonged or night-time breastfeeding. Better knowledge/attitude was associated with the age of the child (p < 0.05), the number of children (p < 0.05) and whether the mother had received advice during pregnancy (p < 0.05). Conclusions The results of this survey show a lack of dental care during pregnancy, a lack of information about oral health from health professionals during and after pregnancy, and consequently gaps in the knowledge needed to care for the oral health of the woman and her child. There is a need for training in oral health for pregnant women and new mothers, but also a need for behavioural change among health professionals who care for pregnant women.